Stem Based Learning Development Design in 2013 Curriculum Integrated by Quran - Gun Gun Ginanjar; Maulana Suhadi (Pancaran Pendidikan, 2018)
The development of 2013 curriculum which is implemented generally expected to be able to create the dimension of attitude, knowledge and skill in teaching and learning process. The dimensions are related to the achievement of educational goal either the activities in the classroom nor in a daily life to make more meaningful learning. The development of STEM (Science, Technology, Engineering and Math) is based on four components KSAV (Knowledge, Skills, Attitude and Value) in accordance with the purpose of 2013 curriculum. STEM curriculum develop the factual, conseptual, procedural and metacognition knowledge integrated in the form of attitude and islamic values by quran approach. The integration pattern is built by webbed based on project related to one concept to another, so it can create the more meaningful learning process and able to be aplied in a daily life.